Efeitos de diferentes intervenções nutricionais e do exercício físico sobre a regulação hormonal da ingestão alimentar e o metabolismo lipídico em ratos - Cheik, Nadia Carla (2005)
The prevalence of obesity is increasing worldwide, indicating that environmental and behavioral aspects play an important causal role. Among the environmental influences, the percentage of fat energy in everyday diet and the lack of physical activity are two important factors, so the mechanisms that control food intake and body weight are essential in public health. The adipose tissue is regulated by several hormones and neuropeptides. Two of these, the circulating peptide hormones leptin and ghrelin, have actions that include reciprocal effects on appetite-regulating neurons in the hypothalamus. This study aimed to observe whether the effects of continuos fedding with a palatable hyperlipidic diet and cycling this diet with a chow one and also entends to design the effects of exercise on these diet regimens.The animals (rats) were assigned to six differents experimental groups:sedentary rats fed with chow diet(SP); exercised rats fed with chow diet(TP); sedentary rats fed with a palatable hyperlipidic diet(SH); exercised rats fed with a palatable hyperlipidic diet(TH); sedentary rats fed with food cycles, alternating weekly the chow diet wih hyperlipidic one(SC); and exercised rats fed with food cycles(TC). The data showed that the two hyperlipidic diet regimens significantly increased RET and EPI weights, area and diameter of adiposity cells, promoted hyperinsulinemia, hyperleptinemia and decreased significantly lipogenesis rate in RET and EPI, showed also percentual reduction in ghrelin levels, but didn t affect the lipolysis rate. In addition, the present investigation showed that chronic exercise decreased body weight gain and adiposity and attenuated insulin, leptin levels in both high-fat feeding regimens, also reduction in ghrelin levels in TP and increased the lipolysis rate under all regimens, excepting in food cycle treatment. Results suggest that diet and exercise affected serum levels anorexigenic and orexigenic hormones and the lipid metabolism.